Beyond Cost Control: How AI-Powered Spend Orchestration Unlocks 7.3% Growth Premiums in 2025 - Simon Suwanzy Dzreke (PT. Maju Malaqbi Makkarana, 2026)
In an uncertain economic climate, a large global retailer used AI-powered spend intelligence to move 220 million from indirect operational costs toward high-impact R&D. In a difficult recession, this decisive step boosted revenue by 11%, demonstrating the transformative impact of effective capital management. This achievement contrasts with